Representation of Women's Struggles in the Film "Imperfect: Career, Love, Scales"(“Imperfect: Karir, Cinta, Timbangan”) - Catur Sunu Wijayanto; Bambang Perkasa Alam; Fitria Iswari (Cultural Syndrome, 2021)
Imperfect Film: Career, Love, Scales is a clear proof that the stigma in society towards body image and other people's expectations of women, especially on the physical appearance of the woman herself, is still very strong. How come? The diversity of tribes and cultures that this nation possesses only refers to one standard of beauty which is quite absurd, at least most men think that women’s standards are the ones who are white, have long hair, tall and slim. This research aims to identify the representation of women's struggles in the Imperfect film: Career, Love, Scales, which raises the issue of insecure/body shaming against women and also instills a message that a perfect life is to accept those imperfections, unless, one would forever live in worry and insecurity. This research method employed John Fiske's semiotic method of reality, representation and ideology which will later be built with the perception of myth through an online correspondence survey methodology regarding with representations of women's struggles in the Imperfectfilm: Career, Love, Scales. The data was collected by using film analysis, internet surfing, documentation and online survey. This present research results point out that the women’s representation of women in the Imperfect film: Career, Love, Scales depicts verbal violence, so the authors suggest that people should eliminate opinions or judgments that can hurt someone both physically and non-physically.